Answer:
(x - 2)(x + 1)(2x -1)
Step-by-step explanation:
We use synthetic division as a tool for factoring the given expression. The coefficients of the terms given are {2, -3, -3, 2}. If x - 2 is a factor of this expression, then 2 is a root. We perform synthetic division as follows:
2 / 2 -3 -3 2
4 2 -2
-------------------------------
2 1 -1 0
Next, we determine whether or not (2x - 1)(x + 1) represents the remaining factor(s). Using -1 as divisor, we get:
-1 / 2 1 -1
-2 1
---------------------
2 -1 0
Since the remainder is zero, x + 1 must be a factor and (2x - 1) the third factor. Answer D is correct.
Step-by-step explanation:
<u>See the missing reasons, in order from top to bottom:</u>
- 1. Definition of rhombus
- 2. Definition of congruent
- 3. Given
- 4. Definition of bisects
- 5. Reflexive property
- 6. SSS (three sides congruency)
- 7. CPCTC
Answer: y - 7 = 1/2 ( x - 2 )
I hope you got a good grade on your assignment!! ^w^
Answer:
mean sample is 9.26
Step-by-step explanation:
Given data
mean = 107 pounds
standard deviation = 39.3 pounds
no of sample (n) = 18
to find out
sample means
solution
according to question we know mean of sample = 107 pounds
so standard error of this sample will be standard deviation /
now put all value n and standard deviation and we get sample mean i.e.
mean sample = standard deviation /
mean sample = 39.3 /
mean sample = 9.26
Answer:
y=-5x+6
Step-by-step explanation:
2y=-10x+12
y=-5x+6